National Survey of Pharmacy Practice at MOH Hospitals in Saudi Arabia 2016-2017: Drug Monitoring and Patients Education - Alomi, Yousef Ahmed; Shorog, Eman; Alshahrani, Asma; Alasmary, Sara; Alenazi, Hadeel; Almutairi, Amani; Almutairi, Masheal (Journal of Pharmacy Practice and Community Medicine)
Objective: To explore National Survey of Pharmacy Practice at MOH hospitals in Saudi Arabia 2016: drug monitoring and patient’s education. Methods: It is a 4-months cross-sectional National Survey of Pharmacy Practice at MOH hospitals in Saudi Arabia. The study consisted of two parts; the demographic information and the second part contained eighty-five questions divided into nine domains drove from American Society of Health-System Pharmacists (ASHP) and Saudi Pharmaceutical Society (SPS) survey, the international standard of Joint Commission of Hospital Accreditation in addition to the local standards of Saudi Center of healthcare accreditation.[1-7] The parts were pharmacy management and resources, prescribing and medication control, preparation of medications and dispensing, Computerized and pharmacy technology, clinical pharmacy services, drug monitoring and patient’s education, Pharmacy inventory control and stock management, Pharmacy education and training, pharmacy total quality management and drug information services. An electronic questionnaire distributed to the one hundred eighty-five directors of pharmacies at MOH hospitals. The study discussed and analyzed National Survey of Pharmacy Practice at MOH hospitals in Saudi Arabia: the drug monitoring and patient’s education. All analyses are done through survey monkey system. Results: The survey questionnaire was distributed to 185 hospitals; the rate of reply was 105 (56.75%). The most type of drug monitoring reporting existed at hospitals was medication error monitoring 80 (80%) followed by patient counseling reporting 72 (79.12%) and drug information inquires 69 (73.4%). The highest type of drug monitoring was patient education reporting (720,000) annually, followed by pharmacist intervention (468,000) annually and a number of prevented medication error per year was (453,600). The most drug monitoring of clinical impact and cost avoidance in the neonates, pediatrics, adults, and geriatrics patients was poisoning information inquiries 59 (56.56%) followed by the pharmacist intervention 52 (57.61%), and drug information inquires 53 (57.61%). The pharmacy patient education given through outpatient services 86 (81.9% and at the bedside during Hospital stay 19 (24.8%) The most Patient Education program 53 (50.5%) covered less than 50% of the bed. The most hospital pharmacies shared in national diabetic world day 62 (59.0%) and national asthma day 30 (28.6%). Conclusion: The pharmacist had the active role in drug monitoring and patient counseling. Expanding the pharmacy services with regular documentation is highly recommended to improve the quality of the services and patient healthcare outcomes.
Keywords: Drug monitoring; Patients education; Ministry of Health; Saudi Arabia